Arrests Without Conviction, 1979-1980: Jacksonville and San Diego - Feeney, Floyd ([Verlag nicht ermittelbar], 1985)
This data collection includes information on robberies and burglaries in two cities, Jacksonville, Florida, and San Diego, California. The unit of analysis is defendants in felony cases. Information on each defendant includes socioeconomic status, criminal history, weapon usage, relationship to victim, trial procedures, and disposition. Demographic information for each defendant includes sex, race, age, and employment status. There are five files in the dataset. Parts 4 and 5 must be merged to form the complete Jacksonville burglaries dataset.